Reverse roots tourism in Argentina: Exploratory research on the Italianity overseas - Cali Falasca, Rocío Belén (2023)
This dissertation explores the phenomenon of Italian reverse roots tourism in Argentina, addressing significant gaps in the existing literature on migration-led tourism. With evidence from participant and non-participant observations, desk research, and in-depth interviews, this study delves into the dynamics of a specific segment of roots tourism, from the demand and supply side. By examining the intersection of personal heritage, tourism, and migration, this thesis sheds light on the interconnections between ancestral ties, cultural affinity, and social imaginaries based on extended forms of kinship in the development of tourism. Furthermore, it identifies the motivations and experiences of Italian tourists engaging in genealogical research or connecting with Italian heritage in Argentina. Fieldwork at the National Immigration Museum served to examine Italian tourists’ forms of engagement with their ancestry. The research undertaken revealed the involvement of various stakeholders in reverse roots tourism, through in-depth interviews with experts at the Museum, Italian cultural associations, and travel agencies. Thematic analysis is employed to process the collected data, enabling the identification of key themes, variations, and patterns. This dissertation shows the significance of genealogy research within reverse roots tourism, uncovering distinct segments that go beyond classical genealogical practices. Furthermore, it demonstrates how the concept of Italianity in Argentina serves as a social imaginary that influences Italian tourists' ethnic background and shapes their tourism experience.